Practical Study of Purification of Lao Cai Wet Process Phosphoric Acid, Based on Tributyl Phosphate (TBP) – Kerosene Mixture Solvent Extraction - Bui, Quang Tuan; Nguyen, Dang Binh Thanh; Nguyen, Trung Dung; Ta, Hong Duc (Old Journal, 2019)
The purification of wet process phosphoric acid using solvent extraction has been widely applied at industrial scale. However, the performance of the purification depends strongly on the solvent characteristics. Common solvents used for the extraction are butanol, hexanol, tributyl phosphate (TBP) and MIBK mixture, … in which TBP/Kerosene have proved to be one of the most efficient solvent mixture. In this work, the effects of temperature, solvation heat, mixing time, and organic/aqueous phase ratio on the extraction of Lao Cai wet process phosphoric acid was studied. The obtained results from experiments that have true potential to apply in the industrial manufacturing process.